HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA WILAYAH KERJA POSYANDU MAWAR DESA KOTA GARO KABUPATEN KAMPAR - Warnis, Resi; Susanti, Komaria; Rahayu, Ary Oktora Sri; Aifa, Wira Ekdeni (Ensiklopedia of Journal, 2025)
Stunting is one of the major public health problems that indicates a failure in child growth due to chronic malnutrition, especially during the first 1,000 days of life. One of the key factors in preventing stunting is the provision of exclusive breastfeeding during the first six months of life. This study aimed to determine the relationship between exclusive breastfeeding and stunting incidence among toddlers in the working area of Posyandu Mawar, Kota Garo Village, Kampar District. This research used a quantitative approach with a retrospective cross-sectional design. The study population consisted of all toddlers who visited Posyandu Mawar in April 2025, totaling 64 children, with 48 selected as samples using accidental sampling techniques. Data were collected through questionnaires and anthropometric measurements, then analyzed using univariate and bivariate analyses with the chi-square test. The results showed that toddlers who were not exclusively breastfed had a 5 times higher risk of experiencing stunting compared to those who were exclusively breastfed (OR = 5; 95% CI = 1.448–17.271; p = 0.020). It can be concluded that there is a significant relationship between exclusive breastfeeding and stunting incidence. The findings of this study are expected to serve as a basis for community education and strengthening exclusive breastfeeding programs at the primary health care level.Keyword : Exclusive breastfeeding, stunting, toddlers